A dual isotopic framework for identifying nitrate sources in surface runoff in a small agricultural watershed, northeast China. (10th February 2020) - Sui, Yuanyuan; Ou, Yang; Yan, Baixing; Rousseau, Alain N.; Fang, Yunting; Geng, Runzhe; Wang, Lixia; Ye, Nan
Abstract: The northeast black soil region of China, an important area of grain production, currently faces serious diffuse pollution issues. In this study, a dual isotopic (δ 15 N and δ 18 O) framework was used to determine nitrate sources in runoff of a small agricultural watershed of this region. The results indicated that the ranges of δ 15 N and δ 18 O values of NO3 -sources were significantly affected by natural geographic features and human activities. Nitrate in cropland runoff was mainly derived from soil, fertilizer and precipitation. Meanwhile, natural inputs, including those of soil and precipitation, represented the main nitrate sources in forest runoff. Domestic sewage, manure and precipitation contributed to most of the nitrate in runoff from villages. In addition, based on runoff export from different land uses and results from a stable isotope mixing model, soil and chemical fertilizer were identified as the main NO3 -source in the whole watershed; suggesting that soil erosion could lead to serious diffuse pollution in the study area. Over all, this study not only provided suggestions to the optimal selection of Best Management Practices (BMPs) in Northeast China, but also could contribute to the identification and quantification of NO3 -sources in agricultural watersheds of the black soil regions worldwide. Graphical abstract: Image 1024 Highlights: Five nitrate sources were identified in surface runoff using a dual isotopic framework. Nitrate isotopic signatures of surface runoff were significantly different among three land use. Both natural and anthropogenic sources contributed to nitrate pollution. Soil and fertilizer were identified as the main nitrate source in the whole watershed.